Legal Consequences of the Determination of Corporate Income Tax Base Referring to IFRS - Jan Molín; Simona Jirásková (European Financial and Accounting Journal, 2014)
This paper is concerned with certain legal consequences of the determination of corporate income tax base. The introductory part analyses the term tax, discusses the constitutional dimensions of taxation, and formulates requirements as to tax legislation. The subsequent part of the contribution discusses the structure of corporate income tax base of those taxpayers, which keep accounting records. Special emphasis is placed on the relationship of accounting revenues and income that is subject to tax. The topic is set in the context of Czech Supreme Administrative Court case law, as the Court has been previously concerned with the issue. Next, we explore the specifics of the determination of a tax base of those taxpayers that are accounting entities, preparing their statutory financial statements in compliance with International Financial Reporting Standards (IFRS).
Keywords: H25; M48; 650; Taxable income; Tax base; International Financial Reporting Standards; Corporate income tax